An inverse Hall-Petch relation in nanocrystalline MgAl2O4 spinel consolidated by high pressure spark plasma sintering (HPSPS). (October 2017) - Sokol, Maxim; Halabi, Mahdi; Mordekovitz, Yuval; Kalabukhov, Sergey; Hayun, Shmuel; Frage, Nachum
Abstract: Inverse Hall-Petch behavior was observed in a transparent nanocrystalline magnesium aluminate spinel ceramic with grain size lower than 30 nm fabricated by high pressure spark plasma sintering (HPSPS). The ceramic was consolidated from 12 nm powder, synthesized by a solution combustion method and displayed an optical transmission of 80% at 550 nm wavelength. The hardness values of the specimens followed the Hall-Petch relation down to a grain size of about 30 nm, reaching a maximal hardness of 20 GPa. The hardness value decreased from 20 to 17.6 GPa when grain size decreased to 17 nm. Graphical abstract: